Profile of Flavonoid and Antioxidant Activity in Cell Suspension Culture of Elaeocarpus grandiflorus - Noor Aini Habibah; Nugrahaningsih Nugrahaningsih; Safitri Safitri; Fajar Musafa; Nur Wijawati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Cell suspension cultures of Elaeocarpus grandiflorus produce flavonoids and various secondary metabolites. Flavonoid profile and antioxidant activity of the suspension culture extract of E. grandiflorus cells have not been studied. Therefore, this research aimed to analyze the antioxidant activity and flavonoid profile of the suspension culture extract of E. grandiflorus cells. Cell suspension cultures of E. grandiflorus were produced from leaf stalk callus that grew on WPM medium with a growth regulator 2.5 ppm 2,4-D. Cells were harvested at 30 days old and then extracted for profile analysis of bioactive compounds using the LC-MS method. The antioxidant activity analysis was conceded out using the DPPH method. The results showed that there were 32 types of flavonoids, of which 11 compounds had a concentration of more than 1% of the total bioactive compounds and had the potential to have antioxidant activity. The analysis results also showed that flavonoids type, composition, and antioxidant activity were not significantly different between the ages of E. grandiflorus cell suspension cultures. In addition, there was no correlation between flavonoid concentration and antioxidant activity. This study enriches information about secondary metabolites production in the E. grandiflorus cell culture which is still very rarely studied because of its rarity. The study also provides potential antioxidant as a scientific basis evident for E. grandifloras cell culture application in medical purpose.